1964
DOI: 10.1128/jb.87.3.720-726.1964
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS OF A GENE CONTROLLING CELL DIVISION AND SENSITIVITY TO RADIATION IN ESCHERICHIA COLI

Abstract: ADl.ER, HOWARD I. (Oak lRidge National Labotatory, Oak Itidge, Tenn.), AND ALICE A. HARDI-CGREE. Analysis of a genetic locus controlling cell division and sensitivity to radiation in Escherichia (o0i. J. Bacteriol. 87:720-726. 1964.-Radiation senisitivity in Eseherichia (oli is under control of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

1968
1968
1977
1977

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(61 citation statements)
references
References 3 publications
0
61
0
Order By: Relevance
“…Therefore, JC355 was treated with NTG, and a mucoid mutant (ES370) was selected on minimal medium at 30 C as described above. This mutant was Plkc sensitive and also T7 sensitive, The mutation to mucoid (excess capsule formation) can occur at two distinct loci: capR (synonomous with Ion; see references 3,14,19) and capS (21). The capR mutants are also UV sensitive (3,9,14).…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, JC355 was treated with NTG, and a mucoid mutant (ES370) was selected on minimal medium at 30 C as described above. This mutant was Plkc sensitive and also T7 sensitive, The mutation to mucoid (excess capsule formation) can occur at two distinct loci: capR (synonomous with Ion; see references 3,14,19) and capS (21). The capR mutants are also UV sensitive (3,9,14).…”
Section: Resultsmentioning
confidence: 94%
“…11. Pantoyl lactone is a division-promoting agent (2,10). Its effect on colony survival can give information about the effect of filament formation on colonyforming ability.…”
Section: Resultsmentioning
confidence: 99%
“…Hirota et al (16) have mapped many division mutants of Escherichia coli and has found no less than seven genetic loci which affect cell division. Others have isolated mutants of cell division (2,3,6,11,16,17,21,23,26,31,32), and in some cases the lesions have been mapped (1,18).…”
mentioning
confidence: 99%